Fenomena Anomali Pasar dan Perilaku Investor dalam Aktivitas Perdagangan Saham di Indonesia - Setyaningrum, Novi Tri; Rusmana, Oman (Journal of Business and Economics Research (JBE), 2025)
Ideally, capital markets operate efficiently, where stock prices reflect all available information. However, in practice, market anomalies often arise that cannot be fully explained by efficient market theory. This study aims to identify and analyze the types of market anomalies occurring in Indonesia, specifically on the Indonesia Stock Exchange (IDX), using a qualitative library research method that employs content analysis and narrative synthesis based on previous studies, books, and relevant scientific sources. The results of the study indicate that several anomalies, such as the day-of-the-week effect, the January effect, market overreaction, and the size effect, still occur in the Indonesian stock market. These findings challenge the assumption of investor rationality and opens up a new discussion regarding behavioral finance approaches. This research contributes to enriching the literature on Indonesian capital market behavior and serves as a reference for investors and regulators in understanding patterns of price irregularities that can influence investment strategies.